Section 3 pesticide labels - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes what a Section 3 pesticide is and how a Section 3 pesticide is registered.
CEPEP 5/02, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticides -- Labeling; Pesticide containers; Pesticides -- Law and legislation